The Bill Buckner Error: Lessons Decades Later - Petit, Francis (Journal of Sports Research, 2020)
The purpose of this research is to determine what lessons, if any, society can learn from the Bill Buckner Error that goes beyond Baseball. The methods of this research include a historical study of the Bottom of the 10th Inning in Game 6 of the 1986 World Series along with the subsequent aftermath for Bill Buckner. The results of this qualitative study indicate that there are learning takeaways for all that go beyond baseball including how Bill Buckner responded to the ordeal and how the passing of time can change perspectives. In addition, a key question that emerged for future research is what impact did the Bill Buckner Error have on the Red Sox trading him away the following season? Furthermore, this research relates to the world of sports in that fans should understand that sports professionals are human and one error along with one moment in time should not define a career.